On Co-Incidence of Plastic (Polythene) Grains in the Gizzard of Semi-Wild (Freely Inhabiting) Common Rock Pigeon, Columba livia intermedia, Linnaeus, 1758, in Biratagar, Nepal - Bhagat, Rakesh Prasad (Tribhuvan University Journal, 2010)
Plastic (polythene) granules of industrial use was obtained in the gizzard of semi-wild (freely inhibitory i.e., not captivated) common rock pigeon. Columba, livia intermidia Linnaeus, 1758, inhabiting at an altitudinal range of 72-80 m in Biratnagar, Nepal while its gizzard was cut open to remove internal content. Since then, gizzard of about 36 such pigeon were cut open to trace granules. In the gizzard of 19 birds, plastic granules were obtained. Such occurrence may be due to hunger or confusion or both or due to overwhelmingly prevalent situation of the present environment. Key Words: Plastic grains; Semi-wild pigeon; Columba livia intermedia; Biratnagar. Tribhuvan University Journal Volume XXVI No. 1, 2009 Page: 81-84